The Firefly guide to minerals, rocks & gems - Hochleitner, Rupert (Firefly Books Ltd., 2019)
The Firefly Guide to Minerals, Rocks and Gems is designed for easy and reliable identification of minerals, gems and rocks. The identification process begins with the stone's streak color, which is how the book is organized: Blue, Red, Yellow, Brown, Green Black and White. Using a sequence of straightforward questions and answers -- aided by over 1,000 photographs and drawings -- the book narrows down the possibilities among 350 minerals, gems and rocks to reach the conclusive classification. Identification is then further narrowed down with respect to Crystal form, Hardness, Luster, Density, Cleavage, Break and Tenacity. Each rock's main photograph shows the general or typical view, and identification tips about features are noted in the margins of the respective page. Similar stones are presented for comparison and tips are provided that can eliminate imposters. Drawings show the mineral's crystal shape. The chemical formula reveals the elements from which the mineral is composed. There is also information about where the stone is typically found and some of the ways that humans have utilized it.